An investigation of living conditions of children living with terminally ill parents due to HIV and AIDS : a case study in Havana informal settlement – Windhoek, Namibia - Kizza, Margaret (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.